(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Drugs have been inhaled for a long time to have a local effect on the mucosa (e.g. Antihistamines, decongestant, vasoconstrictors and antibiotics). Many medications have been proven to achieve a higher systemic bioavailability when administered orally as opposed to nasally in more recent years. It has been demonstrated that several of them replicate the plasma profile as i.v. administration. More recently, systemic delivery of vaccines, hormones, peptides, and other medications has drawn attention to the intranasal route. The pharmacy offers a wide variety of nasal sprays, both over-the-counter and on prescription. Decongestants, glucocorticoids, antihistamines, mast cell stabilisers, saline, and antibiotics are some of them. In this article, nasal sprays are briefly reviewed.